Trichoderma virens-Tv4 enhances growth promoter and plant defense-related enzymes of mungbean (Vigna radiata) against soil-borne pathogen Rhizoctonia solani - Alfi Inayati; Liliek Sulistyowati; Luqman Qurata Aini; Eriyanto Yusnawan (Society for Indonesian Biodiversity, 2020)
Abstract. Inayati A, Sulistyowati L, Aini LQ, Yusnawan E. 2020. Trichoderma virens-Tv4 enhances growth promoter and plant defense-related enzymes of mungbean (Vigna radiata) against soil-borne pathogen Rhizoctonia solani. Biodiversitas 21: 2410-2419. Trichoderma virens has been studied for its ability to control various soil-borne pathogens as well as to induce plant resistance. The ability of T. virens control R. solani and its capability to induce resistance was evaluated in two different genotypes of mungbean (Vigna radiata (L.) R. Wilczek). Plant growth-promoting capability and production of plant defense-related enzymes during plant-pathogen-Trichoderma interaction were investigated. Pathogen infection caused the morphological and biochemical changes as well as increased plant defense enzymes activity such as peroxidase, polyphenol oxidase, PAL, phenolics, and flavonoid compared to control uninoculated plants. T. virens improved mungbean seedling growth in terms of increased total biomass, root weight, and root length as well as improved chlorophyll content and IAA-synthase from leaves and roots. T. virens treatment alone or in the presence of pathogen-induced mungbean defense-related enzymes indicated by the increasing of PO and PPO activity, and higher accumulation of total phenolic and flavonoid content. Although most of plant induced resistance parameters showed low and non-significant in direct single-factor comparison, Pearson’s correlation showed there was a positive correlation between plant growth promoter compounds (IAA and chlorophyll) with plant defense-related enzymes (total phenol, and flavonoid content). T. virens treatment can induce systemic defense response of mungbean seedling directly by increasing the activity of some defense-related enzymes, and indirectly by improving plant health, and promoting plant growth. In conclusion, T. virens-Tv4 has potential to be developed as bio-control agents to control R. solani as well as to induce mungbean resistance.